2021
DOI: 10.26420/austinjnutrifoodsci.2021.1149
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Increase of Body Weight during Covid-19 Breakdown: Data from the Austrian Prevention Project Eddy Kids 2018/19 and Eddy Kids 2019/20

Abstract: Introduction: Overweight and obesity among adults and children has increased dramatically worldwide in the last few decades. Overweight children usually remain overweight in adulthood and develop lots of comorbidities. It is therefore important to take preventive measures as early as possible to counteract this trend. Objective: To find out what effect the temporary school closure in Austria due to COVID-19 had on the school children in terms of body weight. Methods: Anthropometric parameters (bodyweight, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…This study showed rising levels of overweight/obesity during the first pandemic period, as reported in a southern Austrian city [34] and worldwide [13]. Indeed, previous reports from the EDDY study showed that during the onset of the pandemic, children's body weight increased by about 4.5 kg, whereas the previous year, the average increase in body weight was below 3 kg [15]. Moreover, during the strictest period of the lockdown, boys increased 1.67 kg more than girls [35], a fact that was also observed in Klagenfurt, Austria, where boys' increase in BMI SD scores (0.23; 95% CI, 0.18-0.29) was greater than among girls (0.09; 95% CI, 0.04-0.15) [36].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This study showed rising levels of overweight/obesity during the first pandemic period, as reported in a southern Austrian city [34] and worldwide [13]. Indeed, previous reports from the EDDY study showed that during the onset of the pandemic, children's body weight increased by about 4.5 kg, whereas the previous year, the average increase in body weight was below 3 kg [15]. Moreover, during the strictest period of the lockdown, boys increased 1.67 kg more than girls [35], a fact that was also observed in Klagenfurt, Austria, where boys' increase in BMI SD scores (0.23; 95% CI, 0.18-0.29) was greater than among girls (0.09; 95% CI, 0.04-0.15) [36].…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, this study does not include linked samples of participants. The sample belonged to the EDDY ("Effect of sports and diet training to prevent obesity and secondary diseases and to influence young children's lifestyle") study, an intervention study aiming to improve nutrition and physical activity habits by imparting a six-month educational training in 4th-grade students [15]. The EDDY study was initiated by the Austrian Academic Institute for Nutrition in Vienna, Austria, in collaboration with the Institute for Sports and Movement Science at the University of Vienna.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Während der Schulschließungen in der COVID-19-Pandemie 2020 kam es zu einem dramatischen Anstieg des Körpergewichts im Vergleich zur Interventionsphase im Schuljahr 2018/2019 (Abb. 7 ) [ 5 ].
…”
Section: Präventionsprojekt Eddyunclassified
“…Ergebnisse Bisherige Studienergebnisse haben gezeigt, dass eine statistisch signifikante Verbesserung der körperlichen Leistungsfähigkeit 5 , sowie ein verbessertes Ernährungswissen in der Interventionsgruppe durch das EDDY-Projekt 6 erreicht werden konnte. Zudem zeigten die Daten unserer Testungen, dass übergewichtige Kinder einen deutlich höheren Bluthochdruck haben als dies bei Normalgewichtigen der Fall ist 7 .…”
unclassified